Makna Maf’ul Mutlaq dalam Surah Al-Ahzab : Analisis Nahwu dan Sharaf - Hesti Agustin (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This study aims to determine the meanings of maf'ul mutlaq contained in surah Al-Ahzab, as well as knowing the wazan of each maf'ul mutlaq. the method used is a descriptive qualitative approach, with surah Al-Ahzab as primary data, and journals and relevant books as secondary data. The result of this research found 9 maf'ul mutlaq. Of these 9, which means to strengthen the fiil (taukid) is found in 3 verses. While the other 6 verses mean to explain the type (naw'). Of the 9 maf'ul mutlaq, there are also 3 maf'ul mutlaq with فَعَّلَ, 3 with فَعَلَ – يَفْعُلُ, 1 with فَعْلَلَ, 1 with تَفَعَّلَ, and 1 with فَعَلَ – يَفْعَلُ.